Analysis of students challenges and solutions in translating Indonesian text into English - Matilda, Shabrina; ummi nur laila sulistyani (ELT Forum: Journal of English Language Teaching, 2025)
Translating Indonesian text into English is a big deal for Indonesian students, especially with English education students. Previous studies show that general problems among students are idioms, failing to comprehend the text, a lack of vocabulary, and subject-verb agreement. However, it is rare to find their primary concern in non-equivalence problems, and what solutions fit with students based on their experience. In this case, researchers use a qualitative method. To obtain this data, researchers conducted a deep interview using thematic analysis. This method shows that 8th-semester UNNES English Education students also have their biggest concerns and solutions. The problems that students face are grammar, vocabulary, coherence, and cultural issues. Their solutions are also varied; using DeepL and Grammarly for grammar, studying for grammar mastery, using Google and an online dictionary for cultural terms, and using AI to assist in building coherent sentences. It can be seen that most of students used technology for encounter their problem. This discovery can lead to curriculum review to solve students’ translation difficulty and also regulate the digital and AI tools utilization. To enrich the data, future researchers can use another method, or focusing on one type of non-equivalence problem in a kind of text, like news, narrative, procedure, etc.